Generation and Biochemical Characterization of Phase‐Separated Droplets Formed by Nucleic Acid Binding Proteins: Using HP1 as a Model System. Issue 5 (5th May 2021) - Sanulli, Serena; Narlikar, Geeta J.
Abstract: Liquid‐liquid phase separation (LLPS) has been invoked as an underlying mechanism involved in the formation and function of several cellular membrane‐less compartments. Given the explosion of studies in this field in recent years, it has become essential to converge on clear guidelines and methods to rigorously investigate LLPS and advance our understanding of this phenomenon. Here, we describe basic methods to (1) visualize droplets formed by nucleic acid binding proteins and (2) characterize the liquid‐like nature of these droplets under controlled in vitro experimental conditions. We discuss the rationale behind these methods, as well as caveats and limitations. Our ultimate goal is to guide scientists interested in learning how to test for LLPS, while appreciating that the field is evolving rapidly and adjusting constantly to the growing knowledge. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Observing phase‐separated condensates by microscopy. Support Protocol : Coating of glass‐bottom plates. Basic Protocol 2 : Assessing condensate reversibility by changing ionic strength. Alternate Protocol 1 : Assessing condensate reversibility by dilution. Alternate Protocol 2 : Assessing condensate reversibility by altering temperature. Basic Protocol 3 : Quantifying phase separation by centrifugation assay. Basic Protocol 4 : Quantifying phase separation by turbidity assay